Evaluation of Physiological, Haemato-Biochemical Parameters in Tibial Shaft Fracture Repair by Supracutaneous Plating Technique in Cats - Ruchika; Nagaraja, B N; Mahesh, V; M C, Anilkumar; M H, Girish (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study investigated the variations in physiological and haemato-biochemical parameters during fracture healing in six cats with tibial shaft fracture, repaired using supra-cutaneous plating technique. During the study period, physiological parameters were recorded preoperatively and on days 0, 1, 3, 5, 7, 12 and 15 postoperatively, while haemato-biochemical changes were recorded preoperatively and on days 0, 1, 7, 15, 30, 45 and 60 post-operatively. Physiological parameters showed a significant decrease (p<0.05) during the post-operative period, while haematological parameters showed no significant variations during the study. Progressive increase in total erythrocyte count and haemoglobin level were recorded which indicate erythropoiesis. Biochemical evaluation revealed a statistically significant increase (p<0.05) in serum alkaline phosphatase levels on the 15th postoperative day, indicating active osteoblast proliferation during fracture healing. Serum calcium and phosphorus, on the other hand, showed no significant variations in all six cats. Monitoring of biochemical parameters, alongside physical and radiographic evaluations can provide valuable insights for assessing bone healing.